2022
DOI: 10.1177/00031348221074251
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Necrotizing Fasciitis at a Rural Level 1 Trauma Center During the COVID-19 Pandemic

Abstract: Introduction The impact of the COVID-19 pandemic on non‐COVID-19 pathologies has been experienced worldwide. While people appropriately avoided social interactions, many also avoided essential medical care for acute and chronic conditions. This delay in seeking care has been associated with increased morbidity and mortality in several conditions, including life-threatening infections such as necrotizing fasciitis. Methods We retrospectively reviewed the records of patients that presented to the University of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A Spanish study of general surgery reported the same pattern with an increased delay of almost 24 h from the onset of symptoms to arrival at an ED and a decrease in daily cases of emergency general surgeries [15]. Nevertheless, this was contrary to the findings of McGee, et al [16], which showed a 113% increase in cases of NF during the COVID-19 pandemic in the United States. One of the reasons for delayed presentations was patients considered respiratory symptoms of COVID-19 more serious than other non-specific symptoms [17].…”
Section: Discussionmentioning
confidence: 85%
“…A Spanish study of general surgery reported the same pattern with an increased delay of almost 24 h from the onset of symptoms to arrival at an ED and a decrease in daily cases of emergency general surgeries [15]. Nevertheless, this was contrary to the findings of McGee, et al [16], which showed a 113% increase in cases of NF during the COVID-19 pandemic in the United States. One of the reasons for delayed presentations was patients considered respiratory symptoms of COVID-19 more serious than other non-specific symptoms [17].…”
Section: Discussionmentioning
confidence: 85%
“…NF is a serious, rapidly progressive soft tissue infection with Australian mortality rates as high as 18% [ 13 ]. Our review of five cases presenting over a single year reflects the rising incidence of NF globally, likely secondary to the worsening of chronic medical conditions during the Covid-19 pandemic [ 14 ]. Early recognition and early extensive debridement are paramount to successful outcomes.…”
Section: Discussionmentioning
confidence: 99%